2012
DOI: 10.1038/aps.2012.143
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of mTOR activity by LKB1-AMPK signaling in non-small cell lung cancer cells

Abstract: Aim: To investigate the role of LKB1 in regulation of mTOR signaling in non-small cell lung cancer (NSCLC) cells. Methods: LKB1 protein expression and phosphorylation of AMPK, 4E-BP1 and S6K in the cells were assessed using Western blotting in various NSCLC cell lines (A549, H460, H1792, Calu-1, and H1299). Energy stress was mimicked by treating the cells with 2-deoxyglucose (2-DG). Compound C was used to inhibit AMPK activity. Cell growth was measured using the MTS assay. Results: LKB1 protein was expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…It further represents a possible route to therapeutic application for regulating lung cancer progression. In addition, our results are consistent with STK11-mediated activation of AMPK contributing to carcinogenesis (47). We found the knockdown of AMPK and STK11 resulted in similar effects on PDE4D expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It further represents a possible route to therapeutic application for regulating lung cancer progression. In addition, our results are consistent with STK11-mediated activation of AMPK contributing to carcinogenesis (47). We found the knockdown of AMPK and STK11 resulted in similar effects on PDE4D expression.…”
Section: Discussionsupporting
confidence: 90%
“…cAMP is known to activate protein kinase A (PKA)-an AMP-dependent enzyme, then activate enzymes related to metabolic response and regulate gene expression by the activation of transcription factors (such as CREB) (49). An increased intracellular cAMP has also been shown to increase the activity of AMPK (50), which is the direct downstream target of STK11 (LKB1) (47). Further mechanistic studies will be required to understand the relationship among STK11, AMPK, and PDE4D in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study identified AMPK as a potential downstream molecule of LKB1 involved in the mediation of p21/WAF1 induction. We previously revealed that 2-DG treatment potently inhibits the proliferation of LKB1 wild-type lung cancer cells (8). Given the importance of p21/WAF1 in growth arrest, it has been suggested that 2-DG-mediated p21/WAF1 induction may contribute to the inhibitory effect of the compound.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is activated by LKB1 under energy stresses, including adenosine triphosphate (ATP) depletion induced by glycolysis inhibitors. 2-deoxyglucose (2-DG) is a well-characterized glycolysis inhibitor (8). 2-DG is converted by hexokinase to 2-DG-P, which cannot be further metabolized, thus is trapped inside the cell and inhibits hexokinase.…”
Section: Introductionmentioning
confidence: 99%
“…SIVA may affect metabolism by stimulating mTOR signaling, which is known to enhance oxidative metabolism at least in part via activation of S6K and 4EBP1 and consequent translation of nuclear-encoded mitochondrial proteins (34, 35), and to dampen autophagy through phosphorylation and inactivation of the autophagy initiating kinase ULK1/ATG1 (36). Moreover, mTOR is known to promote tumorigenesis in mouse hepatocellular, renal and lung cancer models (28, 29, 37, 38). Thus, a role for SIVA in the positive regulation of mTOR could account for the decreased oxidative phosphorylation, increased autophagy, and reduced tumor burden with Siva deficiency (27, 34, 36, 38).…”
Section: Discussionmentioning
confidence: 99%